Lemony Snicket's A series of unfortunate events [videorecording (DVD)] - Silberling, Bradley; Gordon, Robert, 1960-; Carrey, Jim, 1962-; Aiken, Liam; Browning, Emily, 1988-; Spall, Timothy, 1957-; O'Hara, Catherine; Law, Jude, 1972-; Connolly, Billy; Cedric, the Entertainer, 1965-; Guzmán, Luis, 1956-; Coolidge, Jennifer; et al. (Full screen DVD collection., 2005)
Violet, Klaus, and Sunny Baudelaire are taken in by a series of oddball relatives and others after their wealthy parents are killed in a fire. The first to take them in is the dastardly and cunning Count Olaf, who is only interested in their inheritance.